Evaluation of a youth unsafe driving video: a comparison of two communities. (1st March 2011) - Stewart, T Charyk; Harrington, J; Tanner, D A; Polgar, D; Girotti, M J
Abstract : Objectives: To evaluate and compare the effectiveness of an injury prevention video (iDrive2) designed to raise awareness of youth about the risks and consequences of aggressive, unsafe driving in two Canadian communities, with different injury experiences. Methods: The video with accompanying presentation was delivered to two high schools in different communities. A survey was designed and distributed to students to evaluate program effectiveness. Program components were scored on Likert-scales, with open-ended questions included. Ç 2 and t tests were used to compare groups. Results: There was a total of 651 completed surveys (462 (71%) Brantford; 189 (29%) London)). While <1/3 of each school responded that this was new information, the majority of students (91% Brantford; 83% London; p<0.001) found the program effective in raising awareness of unsafe driving, rating it 5 (London) and 6 (Brantford) out of 7 (p<0.001). The Brantford students were more likely to find the video effective to educate on driving distraction, speeding, drugs and buckling up (p<0.001). More Brantford students reported to better understand risks and learnt strategies (87% vs 69%; 87% vs 70%; p<0.001) and nearly all (97% vs 88%) would recommend the video. Conclusion: While the majority of students found this program effective in raising awareness of unsafe driving (distractions, drugs, speeding, no seatbelt use), the results from Brantford group were more favourable. This high school had a fatal crash involving students in the months preceding the program. The context of this experience created a learning opportunity when students are more receptive, thereby maximising program effectiveness.